Joint Variance Ratio Tests of the Martingale Hypothesis for Exchange Rates - FONG, Wai Mun (Institutional Knowledge at Singapore Management University, 1997)
There is considerable interest in whether exchange rates behave like martingales. Liu and He tested the martingale hypothesis for exchange rates using the variance-ratio methodology of Lo and MacKinlay. They found that exchange rates have violated the martingale property since the inception of floating rates in 1973. Liu and He did not consider the joint implications of their tests, however. In this article, we reassess the martingale hypothesis for exchange rates using the joint tests developed by Hochberg and by Richardson and Smith. Contrary to the findings of Liu and He, the joint tests indicate that the martingale model worked quite well for exchange rates in the recent years of the floating-rate regime.